Ibadat (worships) in Islam: a comparative jurisprudential analysis - Haneef, Sayed Sikandar Shah; Md. Hashim, Ashraf (IIUM Press, 2009)
This book offers a jurisprudential exposition of the acts of worship in Islam based on a comparative analysis of the Muslim jurists` views particularly of the Sunni Schools of Islamic legal thought. Chapter one delineates some key concepts necessary for grasping the intents and purposes of worship from an Islamic viewpoint. Chapter two devotes itself to the discussion of purification, its legal rules and related contemporary questions. Chapter three outlines juridical rules which govern Muslim prayers. Chapter four describes the jurisprudence of fasting together with juristic evaluation of its contemporary issues. Chapter five expounds the classical fiqh of zakah with focus on its application in the modern time. Chapter six examines the juristic rules which regulate hajj and `umrah. The conclusion underlines the basic themes which run throughout the discussion of issues of `ibadat in the book.